2016
DOI: 10.1007/s00520-016-3283-2
|View full text |Cite
|
Sign up to set email alerts
|

Financial burden of colorectal cancer treatment among patients and their families in a middle-income country

Abstract: Despite the high subsidisation in public hospitals, the management of colorectal cancer imposes a substantial financial burden on patients and their families. Moreover, the majority of patients and their families perceive healthcare payments as difficult. Therefore, it is recommended that policy- and decision-makers should further consider some financial protection strategies and support for cancer treatment because cancer is a very costly and chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…While most studies used the broad categories of strategies for coping with healthcare costs commonly covered in international household surveys (eg, using income/savings, borrowing money or selling assets) some drilled down to distinguish between types of borrowing and asset sales 19–28. For example, some studies examined who households borrowed from, noting that those forced to borrow from moneylenders faced higher interest rates than those borrowing from family or friends 25 26 28.…”
Section: Resultsmentioning
confidence: 99%
“…While most studies used the broad categories of strategies for coping with healthcare costs commonly covered in international household surveys (eg, using income/savings, borrowing money or selling assets) some drilled down to distinguish between types of borrowing and asset sales 19–28. For example, some studies examined who households borrowed from, noting that those forced to borrow from moneylenders faced higher interest rates than those borrowing from family or friends 25 26 28.…”
Section: Resultsmentioning
confidence: 99%
“…Our study findings concur with existing studies that financial burden from CRC treatment and follow-up care was one of the key challenges influencing optimal long-term survivorship. [22][23][24] CRC survivors' unmet financial need was highly varied, ranging from insufficient personal coverage on medical claims and cost for colostomy bags and other accessories to having the responsibility to provide some degree of financial security for the family. This underscores the importance of involving clinicians as part of routine follow-up to briefly screen and refer patients to relevant services, as some might not be aware of financial subsidies and assistance that are available.…”
Section: Navigating a Healthcare Journey With Limited Directionmentioning
confidence: 99%
“…Notably, according to our survey, some lung cancer patients still have no medical insurance, and their CCE was paid entirely out of pocket. A study investigating the financial burdens of cancer patients showed that 94.2% of cancer patients at the diagnosis stage and 86.2% of cancer patients at six months after diagnosis found their financial burden to be at least somewhat difficult to handle 44. Thus, we can surmise that the plight and financial burden of lung cancer patients without medical insurance in China are worse than those who have medical insurance.…”
Section: Discussionmentioning
confidence: 98%